2021
DOI: 10.36129/jog.33.03.05
|View full text |Cite
|
Sign up to set email alerts
|

NR2F6, LOXL2 and DMBT1 expression in cervical cancer tissues, prognostic and clinicopathological implications

Abstract: Background. Detection of novel predictive markers for early detection of lymph nodes metastases in cervical cancer is very important. Disturbed NR2F6 expression was found in many cancers playing different roles according to cancer type. LOXL2 was incriminated in cancer progression and unfavorable survival in many cancer types. Decreased DMBT1 expression was found in many cancers during their progression. Aim of the present work was to assess expression of NR2F6, LOXL2 and DMBT1 in cervical cancer tissues using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In a retrospective multi-institutional study, patients with high grade HR-HPV-negative cervical dysplasia have more favorable outcomes than patients with documented HR-HPV infection [33]. Furthermore, deregulation of some genes such as NR2F6, LOXL2 and DMBT1, could lead to unfavorable oncological outcomes in patients with cervical cancer [34]. A multicenter study has confirmed that preoperative conization could play a protective role in the risk of disease recurrence in patients with an early stage cervical cancer (IB1) [35].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective multi-institutional study, patients with high grade HR-HPV-negative cervical dysplasia have more favorable outcomes than patients with documented HR-HPV infection [33]. Furthermore, deregulation of some genes such as NR2F6, LOXL2 and DMBT1, could lead to unfavorable oncological outcomes in patients with cervical cancer [34]. A multicenter study has confirmed that preoperative conization could play a protective role in the risk of disease recurrence in patients with an early stage cervical cancer (IB1) [35].…”
Section: Discussionmentioning
confidence: 99%
“…There is only little data regarding the prognosis of these patients, however the main prognostic factor seems to be the initial stage of the disease: as later is the diagnosis as worse is the prognosis. Due to the rarity of extranodal cervical NHL, there is no consensus in the literature concerning the optimal management of cervical extranodal NHL [10].…”
Section: Review Of Literature (Table 1)mentioning
confidence: 99%